Predatory behavior, nesting habits, and impacts on honey bees (Apis mellifera) of an invasive hornet (Vespa tropica) on the island of Guam - Rosario, Christopher A.; Otis, Gard W.; Miller, Ross H.; Groover-Landis, Arianna A.; Stanley, Ella S.; Mattila, Heather R. (PloS one, 2025)
Hornets (genus Vespa ) are a conspicuous taxon of large eusocial wasps that are predators of other insects. Increasingly, hornets are gaining notoriety as damaging invaders after repeated introductions into novel habitats. Most hornets are highly effective predators, so they have the potential to greatly impact local entomofauna, including economically important pollinators. In 2016, Vespa tropica , a hornet with a broad natural range throughout subtropical and tropical Asia, was detected on Guam, although few details have been published since the initial alert. We provide the first comprehensive update on the status and impact of V. tropica hornets on Guam based on nine years of beekeeper and public reports, as well as field collections of nests, hornets, and videos of hunting behavior in managed apiaries. We show that the population of non-native V. tropica is established and thriving on Guam. Nests were found in a diversity of sites: below and above ground, sheltered and exposed, and in urban and greenspaces. V. tropica was a year-round predator in apiaries, with up to 12% of colony losses per year attributed to hornet attacks. Notably, hornets often attacked single honey bee ( Apis mellifera ) colonies in groups, similar to the hunting strategy of their close relatives, the giant hornets Vespa mandarinia and Vespa soror . Hornets killed defending workers, eventually weakening colonies and entering hives to consume bee brood. Bees mounted defenses that included alarm piping, bee ‘carpets’, and attempts to ball hornets. Hornets were active all year, but were significantly more active during the wet season (July‒December). Preliminary analysis of color forms suggested that the source of V. tropica on Guam is likely continental southeast Asia, although genetic analyses are required. Our study reveals that Guam is facing a fierce invader in V. tropica , which is placing strong predatory pressure on pre-established honey bees.